Recent advances and applications in alternative investments - Zopounidis, Constantin; Kenourgios, Dimitris, 1973-; Dotsis, George, 1976- (Advances in finance, accounting, and economics (AFAE) book series., 2020)
"This book explores theoretical and empirical advances and applications in alternative investments"--